Collagen VII Expression Is Required in Both Keratinocytes and Fibroblasts for Anchoring Fibril Formation in Bilayer Engineered Skin Substitutes. Issue 9 (September 2019) - Supp, Dorothy M.; Hahn, Jennifer M.; Combs, Kelly A.; McFarland, Kevin L.; Schwentker, Ann; Boissy, Raymond E.; Boyce, Steven T.; Powell, Heather M.; Lucky, Anne W.
The blistering disease recessive dystrophic epidermolysis bullosa (RDEB) is caused by mutations in the gene encoding collagen VII (COL7), which forms anchoring fibrils that attach the epidermis to the dermis. Cutaneous gene therapy to restore COL7 expression in RDEB patient cells has been proposed, and cultured epithelial autograft containing COL7-modified keratinocytes was previously tested in clinical trials. Because COL7 in normal skin is expressed in both fibroblasts and keratinocytes, cutaneous gene therapy using a bilayer skin substitute may enable faster restoration of anchoring fibrils. Hypothetically, COL7 expression in either dermal fibroblasts or epidermal keratinocytes might be sufficient for functional anchoring fibril formation in a bilayer skin substitute. To test this, engineered skin substitutes (ESS) were prepared using four combinations of normal + RDEB cells: (1) RDEB fibroblasts + RDEB keratinocytes; (2) RDEB fibroblasts + normal keratinocytes; (3) normal fibroblasts + RDEB keratinocytes; and (4) normal fibroblasts + normal keratinocytes. ESS were incubated in vitro for 2 weeks prior to grafting to full-thickness wounds in immunodeficient mice. Biopsies were analyzed in vitro and at 1, 2, or 3 weeks after grafting. COL7 was undetectable in ESS prepared using all RDEB cells (group 1), and macroscopic blistering was observed by 2 weeks after grafting in ESS containing RDEB cells. COL7 was expressed, in vitro and in vivo, in ESS prepared using combinations of normal + RDEB cells (groups 2 and 3) or all normal cells (group 4). However, transmission electron microscopy revealed structurally normal anchoring fibrils, in vitro and by week 2 in vivo, only in ESS prepared using all normal cells (group 4). The results suggest that although COL7 protein is produced in engineered skin when cells in only one layer express the COL7 gene, formation of structurally normal anchoring fibrils appears to require expression of COL7 in both dermal fibroblasts and epidermal keratinocytes.